1995
DOI: 10.1002/adma.19950070230
|View full text |Cite
|
Sign up to set email alerts
|

CH…S and S…S: Two major forces in organic conductors

Abstract: The packing in molecular crystals is determined by intermolecular interactions. An understanding of these interactions would enable the design of systems exhibiting effective conductivity and superconductivity. By careful analysis of the shortest intermolecular interactions in the crystal combined with accurate ab‐initio calculatins it has been shown that CH…X and S…S are the two interactions most likely to influence the structures of these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 20 publications
5
81
0
Order By: Relevance
“…On the other hand, the packing of the neutral crystals is a compromise between the S´´´S interactions and the competing CÀH´´´S ones. [14] Notice also that both d SÀS distributions are similar to those found by Gavezzotti et al [7d] in a much broader subset of crystals. Therefore, the S´´´S interactions in TTF-based crystals can be modeled by the Figure 2, within the TTF-based neutral crystals.…”
Section: Resultssupporting
confidence: 81%
“…On the other hand, the packing of the neutral crystals is a compromise between the S´´´S interactions and the competing CÀH´´´S ones. [14] Notice also that both d SÀS distributions are similar to those found by Gavezzotti et al [7d] in a much broader subset of crystals. Therefore, the S´´´S interactions in TTF-based crystals can be modeled by the Figure 2, within the TTF-based neutral crystals.…”
Section: Resultssupporting
confidence: 81%
“…In contrast to the octahedrally coordinated Na atoms (two N and four O atoms) in salt 1, the lithium ions in 2 are À unit exhibits two Se¥¥¥HÀC contacts (Se1¥¥¥H4ÀC4 3.015 ä, q = 1558) [20] between the H atoms of the pds ligand and the closest Se atoms of the perpendicular complexes of the neighboring stacks. At the same time each complex shows two strong N¥¥¥H À OH hydrogen bonds (N2¥¥¥H À O 1.948 ä, q = 1768) [21] between the uncoordinated N atom and the H atom of a water molecule that belongs to the coordination sphere of the Li atom.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, one-dimensional chains of alternating Na ions and two water molecules along a are formed between the parallel stacks of [Cu III (pdt) 2 ] À complexes (Figure 8). À unit has four short S¥¥¥HÀC contacts (S1¥¥¥H3ÀC3 2.873 ä, q = 1638; S2'¥¥¥H4ÀC4 2.985 ä, q = 1298) [20] between the H atoms of the pdt ligand and the closest S atoms of the perpendicular complexes of the neighboring stacks. At the same time each complex shows two moderately strong N¥¥¥HÀOH hydrogen bonds (N2¥¥¥HÀO 2.142 ä, q = 1468) [21] between the uncoordinated N atom and the H atom of a water molecule that belongs to the coordination sphere of the Na atom.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that besides close S ¥¥¥ S contacts, C À H ¥¥¥ S, C À H ¥¥¥ p and p ± p stacking contribute to the solid-state structures. [30] The examination of the S ¥¥¥ S distances and the resulting configurations of a series of compounds belonging to the type R-S-R' with R,R'=H could be rationalized in terms of electrophilic ± nucleophilic interactions of different sulfur centers, or by considering the corresponding frontier orbitals ( Figure 5). [25,31] In most cases the arrangement of the planes, defined by R, S, and R', was that one R-S-R' unit (say the electrophile) approaches the other R-S-R' unit (the nucleophile), in such a way that both planes are nearly perpendicular to each other ( Figure 5).…”
Section: Van Der Waals Forcesmentioning
confidence: 99%